Cautivos de los Discursos: Parodia de la Novela Histórica Post-Dictatorial en El Placer de la Cautiva de Leopoldo Brizuela. Issue 3 (3rd July 2018) - Tokarz, Wojciech
Abstract: After the fall of the last dictatorship in Argentina, the historical novel has undergone profound transformations encouraging literary critics to associate it with the process of the redemocratization of the region. Indeed, the genre can be seen to express an important political dimension promoting democracy, diversity, and inclusion. It can, on occasion, rewrite national history and include new and often unorthodox perspectives on the past, thereby rescuing traditionally marginalized groups from oblivion. However, the fictionalization of history and the transformation of its discourse are formulated from a perspective deeply rooted in modernity, and the democratic project extrapolated from these novels is limited, therefore, to a mere reorganization of traditional discourses that persistently excludes groups of non-European heritage from the national project. The short novel El placer de la cautiva by Leopoldo Brizuela, analyzed in this article, offers a parody of the genre that draws on the disconnect between the democratic dimension of historical fiction and the ongoing marginalization of indigenous peoples in Argentina.